1994
DOI: 10.1002/cne.903490408
|View full text |Cite
|
Sign up to set email alerts
|

Size‐related colocalization of glycine and glutamate immunoreactivity in frog and rat vestibular afferents

Abstract: Presence and distribution of glutamate, glycine, GABA and beta-alanine in VIIIth nerves of frogs and rats were investigated with postembedding immunocytochemical methods on serial semithin sections. In Scarpa's ganglion of the frog, all cell bodies were glutamate immunoreactive. About 17% of the cells per section were also glycine immunoreactive, but none were GABA or beta-alanine immunoreactive. The mean diameter of glycine-positive cell bodies (26.7 +/- 6.9 microns; N = 130) was significantly (P < 0.0001) la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
20
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 45 publications
(49 reference statements)
3
20
0
Order By: Relevance
“…Vestibular neurons receive excitatory glutaminergic input from the vestibular nerve [7] and commissural excitatory afferents [8]. Immunohistochemical and in situ hybridization histochemical studies revealed the highest glutamate receptor 2 (GluR2) expression in giant Deiter's neurons of the lateral vestibular nucleus and the lowest expression in small neurons throughout the vestibular nuclei [9].…”
Section: Discussionmentioning
confidence: 99%
“…Vestibular neurons receive excitatory glutaminergic input from the vestibular nerve [7] and commissural excitatory afferents [8]. Immunohistochemical and in situ hybridization histochemical studies revealed the highest glutamate receptor 2 (GluR2) expression in giant Deiter's neurons of the lateral vestibular nucleus and the lowest expression in small neurons throughout the vestibular nuclei [9].…”
Section: Discussionmentioning
confidence: 99%
“…Based on fundamental differences in locomotor performance of frog and mouse, an additional set of glycinergic vestibular commissural neurons in the latter might also be an expression of the necessity for a more efficient commissural push-pull modulation of vestibular activity during the more or less continuous mammalian-type locomotion. Alternatively, GlyT2 transporterexpressing vestibular neurons in the YFP-16 mouse (Bagnall et al, 2007) might be a specific population of excitatory vestibular commissural neurons that colocalize glutamate and glycine as a subgroup of frog and rat vestibular nerve afferents (Reichenberger and Dieringer, 1994), although mouse GlyT2-positive vestibular neurons were VGluT2 negative.…”
Section: Pharmacological Profile Of Vestibular Commissural Pathwaysmentioning
confidence: 99%
“…The antibodies had a high selectivity, and only the glycine antiserum exhibited a weak cross-reactivity with conjugated ¬-alanine. All antibodies have been tested previously in frog material (Reichenberger et al, 1993;Reichenberger and Dieringer, 1994).…”
Section: Antibody Characterizationmentioning
confidence: 99%
“…Afferent vestibular nerve input is mediated by glutamate or a related substance via glutamate receptors of the NMDA and non-NMDA subtypes in frogs (Cochran et al, 1987;Reichenberger and Dieringer, 1994;Straka et al, 1996a,b) and rats (Kinney et al, 1994). Abducens motoneurons and internuclear neurons are inhibited by uncrossed, glycinergic vestibular neurons in frog as well as in cat (Straka and Dieringer, 1993;Spencer et al, 1989).…”
mentioning
confidence: 97%
See 1 more Smart Citation